Chlorella sorokiniana induces mitochondrial-mediated apoptosis in human non-small cell lung cancer cells and inhibits xenograft tumor growth in vivo. Issue 1 (December 2017) - Lin, Ping-Yi; Tsai, Ching-Tsan; Chuang, Wan-Ling; Chao, Ya-Hsuan; Pan, I-Horng; Chen, Yu-Kuo; Lin, Chi-Chen; Wang, Bing-Yen
Abstract Background Lung cancer is one of the leading causes of cancer related deaths worldwide. Marine microalgae are a source of biologically active compounds and are widely consumed as a nutritional supplement in East Asian countries. It has been reported that Chlorella or Chlorella extracts have various beneficial pharmacological compounds that modulate immune responses; however, no studies have investigated the anti-cancer effects of Chlorella sorokiniana (CS) on non-small cell lung cancer (NSCLC). Methods In this study, we evaluated the anti-cancer effects of CS in two human NSCLC cell lines (A549 and CL1-5 human lung adenocarcinoma cells), and its effects on tumor growth in a subcutaneous xenograft tumor model. We also investigated the possible molecular mechanisms governing the pharmacological function of CS. Results Our results showed that exposure of the two cell lines to CS resulted in a concentration-dependent reduction in cell viability. In addition, the percentage of apoptotic cells increased in a dose-dependent manner, suggesting that CS might induce apoptosis in human NSCLC cells. Western blot analysis revealed that exposure to CS resulted in increased protein expression of the cleaved/activated forms of caspase-3, caspase-9, and PARP, except caspase-8. ZDEVD (caspase-3 inhibitor) and Z-LEHD (caspase-9 inhibitor) were sufficient at preventing apoptosis in both A549 and CL1-5 cells, proving that CS induced cell death via the mitochondria-mediated apoptotic pathway. Exposure of A549 and CL1-5 cells to CS for 24 h resulted in decreased expression of Bcl-2 protein and increased expression of Bax protein as well as decreased expression of two IAP family proteins, survivin and XIAP. Conclusions We demonstrated that CS induces mitochondrial-mediated apoptosis in NSCLC cells via downregulation of Bcl-2, XIAP and survivin. In addition, we also found that the tumors growth of subcutaneous xenograft in vivo was markedly inhibited after oral intake of CS.